Termo de ajustamento de conduta para o gerenciamento de resíduos sólidos: uma breve análise sobre o caso do fechamento do “Lixão” do Aurá no município de Belém - RIBEIRO, César Augusto Lopes (2022)
The present work sought to bring an analysis on the Conduct Adjustment Term, reporting the case that occurred with the closure of the Aurá dump and the problem that still exists in the metropolitan area of Belém about the correct destination and treatment of solid waste. In the pursuit of this objective, a qualitative bibliographic search was used, seeking the most important and updated information on the topic. Aiming at this objective, the work was divided into three chapters: at first, it was treated about the current Brazilian scenario on the issue of solid waste, the national policy implemented with Law 13.305 / 2010 and its definitions, in a second moment, the implementation of the PNRS, the history of the Aurá dump, its closure and the social problem caused, ending with the conduct adopted by the Public Ministry in an attempt to resolve the case. Law 12,305 of 2010 implemented in Brazil the National Solid Waste Plan aiming at the correct destination of the waste generated in the most diverse means, focusing on objectives such as non-production, reduction of waste, reuse, recycling and final disposal in an environmentally correct location for this purpose. end. The law made it mandatory to close the dumps around the country, including the Aurá dump, one of the largest in activity at the time. However, in order for the provisions to be met, there was a need to establish a Term of Conduct, formulated by the Public Prosecutor of Pará, allowing time for the city halls of the metropolitan region of Belém to adapt to the rules of the current legislation, something that until the present date has not been fully realized.